Profile of nurse managers of the hemodialysis service of a private institution in the northern region (Research, Society and Development, 2020)
Objective: to describe the role of nurse managers and their legal implications in private institutions in northern Brazil. Method: Descriptive study with a qualitative approach carried out with nurse managers of private dialysis institutions in Belém. For the interpretation of the data, Bardin's content analysis was used. Result: The profile of the nurses found are younger professionals who have a long time of experience in the place and a longer time of training. The categories arising from the content analysis were: Category 1- Functions performed by nurses in the dialysis unit; Category 2- Knowledge of the legal implications of nurses in hemodialysis. Conclusion: It was noticed that nurses often assume functions that are not compatible with the position, that is, they supply and fill the gap of other professional demands and service needs.